The general nilpotent operator system - Dombi József (FUZZY SETS AND SYSTEMS, 2015)
Abstract In this paper we show that a consistent logical system generated by nilpotent operators is not necessarily isomorphic to Łukasiewicz-logic, which means that nilpotent logical systems are wider than we have thought earlier. Using more than one generator functions we examine three naturally derived negations in these systems. It is shown that the coincidence of the three negations leads back to a system which is isomorphic to Łukasiewicz-logic. Consistent nilpotent logical structures with three different negations are also provided.